Social ‘Capitalising’ the COVID-19 Pandemic: A Portrait of Three Zimbabwean Female Musicians - Butete , Victoria Blessing (Springer, Cham, 2022)
Social capital is the currency through which agents compete for access to other forms of capital in the field. Drawing on my doctoral research into the government’s role in Zimbabwe’s live music sector, this study examines how social capital impacted the musical careers of three Zimbabwean female musicians during the COVID-19 pandemic. It assesses how these musicians utilised their social capital to traverse their COVID-19 circumstances. I employed a case study-based qualitative research design, and I gathered data through in-depth semi-structured interviews. The overarching finding was that the COVID-19 pandemic impacted the three Zimbabwean female musicians differently and in both positive and negative ways. Overall, the loss of live music performance opportunities had negative economic, social and cultural impacts. It forced them to regenerate their human capital by learning new skills. The learning process augmented their extant social capital and enhanced their proficiency as they created new COVID-19-friendly networks. They utilised their cognitive, bonding, bridging, linking, relational and structural forms of social capital to exploit and expand existing networks. Henceforth, social capital, albeit to varying degrees, sustained the three Zimbabwean female musicians by allowing them access to economic, cultural and symbolic capital during the COVID-19 pandemic.